Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1177/10892532221093955
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Organ Transplantation: Noteworthy Literature in 2021

Abstract: This review highlights noteworthy literature pertinent to anesthesiologists and critical care physicians caring for patients undergoing abdominal organ transplantation. In 2021, we identified noteworthy papers from over 1,200 peer-reviewed publications on pancreatic transplantation, over 1,400 on intestinal transplantation, and over 9,000 on kidney transplantation. The liver transplantation section focuses on clinical trials and systematic reviews and meta-analyses published in 2021 and features 20 selected pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…6 The importance of central venous access in intestinal transplantation cannot be overstated—the authors review an article that describes the use of non-conventional vascular access (NCVA) for this patient population as a way to ensure ongoing venous access for long-term parenteral nutrition. 6…”
Section: Abdominal Transplantationmentioning
confidence: 99%
See 4 more Smart Citations
“…6 The importance of central venous access in intestinal transplantation cannot be overstated—the authors review an article that describes the use of non-conventional vascular access (NCVA) for this patient population as a way to ensure ongoing venous access for long-term parenteral nutrition. 6…”
Section: Abdominal Transplantationmentioning
confidence: 99%
“…They point out that the utility of these risk indices may not be as useful in this particular patient population and the presence of certain risk factors including prior CVD history, diabetic nephropathy, age, duration of dialysis, hypoalbuminemia, proteinuria, and prior angina may indicate higher risk for peri-operative MACE. 6 However, despite these risk factors for increased risk of perioperative cardiac events, an ongoing trial performed a post hoc analysis that found no difference in mortality or non-fatal MI in patients who received revascularization for stable ischemic heart disease with inducible ischemia vs medical therapy alone. 6 The authors also report on a study evaluating pre-operative mean arterial pressure (MAP) and its relation to delayed graft function (DGF); unsurprisingly, patients with pre-operative MAP <80 were more likely to have DGF.…”
Section: Abdominal Transplantationmentioning
confidence: 99%
See 3 more Smart Citations